Computational Simulations to Predict the Morphology of Nanostructures and Their Properties - Laranjeira, José A. S. [UNESP] (2022)
The ability to synthesize nano and nanocrystals with well-defined morphologies with good homogeneity is essential for applications that depend on electronic, optical, magnetic, catalytic and/or chemical properties. The morphology determines the types of interfaces generated with the external environment. However, controlling the shape and size of nanocrystals is a complex process not only depending on the chemical formula and structure, but also on external conditions that can be or not controllable. The nanocrystals surfaces have distinct atomic structures and electronic properties and, consequently, these properties can be controlled by modifying their morphology. Within this context, Wulff's construction can be used to estimate the relation of the electronic, structural, and energetic properties with the morphologies. In addition, this method allows the study of growth mechanisms of metals, binary oxides, and complex crystals. This methodology can be applied to an infinity of materials, in special, the molybdates (AMoO4) and tungstates (AWO4) family, that urges from the combination of the (MoO4)−2 or (WO4)−2 ions, respectively, with a bivalent cation (A2+). These materials have attracted great interest because of their applications in photoluminescence, photocatalysis, sensors and loads of storage devices; in addition to having high thermochemical stability and being subject to changes in their optical and dielectric properties from doping with transition metals or rare earths. In this sense, this chapter presents the study of the property/morphology relationship of these materials studied according to computational simulations of the most exposed surfaces so that each surface can be characterized through its structural and electronic properties, together with the relative stabilities.